2007
DOI: 10.4049/jimmunol.178.9.5652
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid DNA Vaccine-Elicited Cellular Immune Responses Limit In Vivo Vaccine Antigen Expression through Fas-Mediated Apoptosis

Abstract: Particularly potent cellular or humoral immune responses are needed to confer protection in animal models against such pathogens as HIV/SIV, Mycobacterium tuberculosis, and malarial parasites. Persistent, high-level vaccine Ag expression may be required for eliciting such potent and durable immune responses. Although plasmid DNA immunogens are being explored as potential vaccines for protection against these pathogens, little is known about host factors that restrict long-term plasmid DNA vaccine Ag expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 37 publications
(40 reference statements)
4
38
1
Order By: Relevance
“…Animal whole blood was used to perform a pentamer analysis to evaluate F-specific CD8 response. Similar to the previous outcome with DNA vaccine (22), our pentamer analysis (Supplemental Fig. 1) indicated, over 1 wk after the immunization, that high-level expression of luciferase corresponded to imperceptible F-specific CD8 + T cell response.…”
Section: Early In Vivo Ag Expression At Site Of Injectionsupporting
confidence: 85%
See 1 more Smart Citation
“…Animal whole blood was used to perform a pentamer analysis to evaluate F-specific CD8 response. Similar to the previous outcome with DNA vaccine (22), our pentamer analysis (Supplemental Fig. 1) indicated, over 1 wk after the immunization, that high-level expression of luciferase corresponded to imperceptible F-specific CD8 + T cell response.…”
Section: Early In Vivo Ag Expression At Site Of Injectionsupporting
confidence: 85%
“…1A, 1B), but not luciferase alone, indicating that the nature of the Ag can affect expression kinetics at later time points after administration (from days 7 to 14). This is reminiscent of previous findings obtained with DNA vaccines suggesting that an adaptive immune response directed toward the foreign protein expressed can lead to immunemediated clearance of cells expressing the Ag (22).…”
Section: Early In Vivo Ag Expression At Site Of Injectionsupporting
confidence: 72%
“…In addition, we observed that vaccine antigen expression persists in Fas receptor knockout mice, suggesting a role in this process for T cell-mediated apoptosis via the Fas/FasL pathway. 3 Based on these data, we hypothesized that CD8 ϩ T cells mediated vaccine antigen clearance through Fas-dependent apoptosis. Alternatively, other studies have suggested that the limited antigen expression in this setting may be a result of antibody-dependent cell-mediated cytotoxicity or complement-mediated lysis.…”
Section: Introductionmentioning
confidence: 99%
“…Vectors and Immunization-The plasmid DNA-Luciferase (DNA-Luc) construct with the AL11-Gag tag was constructed as described previously (27). This vector contains the GL4.10 luciferase gene (Promega, Madison, WI) and the immunodominant H-2D b -restricted SIV-Gag AL11 epitope flanked by triple alanine spacers.…”
Section: Methodsmentioning
confidence: 99%